Synthesis and characterization of new cholinium-based ionic liquids for antimicrobial application - Jumbri, Khairulazhar; Mah Noh, Nor Suzy Farahana; Ahmad, Nur Afiqah; Abdul Rahman, Mohd Basyaruddin; Ahmad, Haslina (Akademia Baru, 2018)
A series of new cholinium-based ionic liquids (ILs) was synthesized by using simple neutralization reaction. The synthesized ILs were choline 3,5-dinitrosalicylate, choline gallate, choline s-(+)-2-(4-isobutylphenyl)propionate, choline behenate and choline peracetate. All the synthesized cholinium-based ILs were characterized by using FT-IR, 1 H and 13C NMR, mass spectrometry, thermogravimetric and differential scanning calorimetry. Result obtained from all characterization techniques confirmed the formation of these cholinium-based ILs. These ILs were then tested for their antimicrobial properties. Anti-microbial test was carried out towards seven types of bacteria which consist of three Gram-positive bacteria, Bacillus subtilis (B29), Staphylococcus aureus (S276), Staphylococcus epidermidis (S273), two Gram-negative bacteria, Pseudomonas aeruginosa (ATCC 15442) and Escherichia coli (E266) and two types of yeasts, Candida albicans (9002) and Candida tropicalis (A3). Streptomycin and Nystatin were used for all bacteria as standard. There is one cholinium-based IL shows excellent inhibition of microbes from growth. Choline peracetate was found to inhibit Candida albicans (9002) as good as the standard, Streptomycin which perform highest of inhibition zone diameter, 25 mm.